Réponses

2013-09-29T18:41:33+02:00
Exercice 2 :
A = 3 ( 2x - 4 ) + 5 ( 3 - x)
= 3 * 2x + 3 * (-4) + 5 * 3 + 5 * (-x)
= 6x + (-12) + 15 + (-5x)
= 1x + 3 
 
B = 2x ( 5 + 3x ) - 4 ( x + 5)
= 2x * 5 + 2x * 3x - 4 * x + (-4) * 5
= 10x +  6x^{2} - 4x + (-20)
= 6x +  6x^{2} - 20

Exercice 3 :
A = ( 4x - 8 ) - ( 3x - 7 ) + ( -2x + 3 )
 = 4x * 3x + 4x * 8 + (-8) * 3x + (-8) * (-7) - 3x * (-2x) + 3x * 3 + (-7) * (-2x) + (-7) * 3
 12x^{2} + 32x + (-24x) + 56 + 6x^{2} + 9x + 14x + (-21)
 18x^{2} + 31x + 35

B = 

EDIT : Je reprend dans - de 20 minutes